FACTORS ASSOCIATED WITH THE COMPLETENESS OF DIPHTHERIA IMMUNIZATION (DPT) IN INFANTS IN THE WORKING AREA OF KUTA BARO HEALTH CENTER, ACEH BESAR DISTRICT - Anwar, Anwar; Anwar, Syarifuddin; Arbi, Anwar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: Diphtheria, pertussis, and tetanus (DPT) immunization is considered effective in enhancing immunity against diphtheria. Kuta Baro Subdistrict has a DPT immunization coverage among infants that remains below the target, posing a risk of diphtheria outbreaks. This study aimed to identify factors associated with the completeness of DPT immunization at the Kuta Baro Health Center. Method: This was a descriptive analytic study with a cross-sectional design. The population included 41 mothers whose babies had received the first dose of DPT immunization in Kemukiman Lamblang, with the entire population serving as the sample. Data were collected through interviews and observation. Statistical analysis was performed using the Chi-square test with a significance level of α=0.05. Result: A total of 29.3% of infants had incomplete DPT immunization. Factors identified included lack of maternal knowledge (56.1%), long distance to health facilities (26.8%), insufficient family support (29.3%), suboptimal role of health workers (43.9%), and occurrence of immunization side effects (43.9%). Statistical analysis showed significant associations between immunization completeness and knowledge (p=0.024), distance to health services (p=0.031), family support (p=0.009), role of health workers (p=0.010), and immunization side effects (p=0.001). Recommendation: It is recommended that the Head of Kuta Baro Health Center improve education and counseling efforts regarding the benefits of DPT immunization for mothers and the broader community in order to increase DPT immunization coverage.